Dinamika Organizational Citizenship Behavior melalui Lensa Social Exchange Theory : Analisis Work-Life Balance, Gaya Kepemimpinan dan Motivasi Intrinsik pada Industri Perbankan Daerah - Luthfi Arie Widzayanto; Inka Nuromavita; Dina Ulayya Aziizah; Maulia Regita Belananda (Yayasan Literasi Sains Indonesia, 2026)
This study aims to analyze the effects of Work-Life Balance (WLB), Leadership Style (LS), and Intrinsic Motivation (IM) on Organizational Citizenship Behavior (OCB) among employees of PT. BPR BKK Kendal. The research population consisted of 92 employees, all of whom were included as respondents using a saturated sampling technique. Data were collected through a questionnaire using a 5-point Likert scale and analyzed using (PLS-SEM) with SmartPLS 3. The results indicate that WLB, LS, and IM have positive and significant effects on employees’ OCB. Work-Life Balance contributes to increased employee satisfaction and engagement, which encourages voluntary behavior and extra-role contributions to the organization. A communicative and responsive leadership style fosters employee loyalty and initiative in performing tasks beyond formal job responsibilities. Intrinsic motivation strengthens discretionary behavior as employees are driven by internal satisfaction and personal achievement. These findings support the application of Social Exchange Theory in human resource management, emphasizing that organizational attention to employee well-being, effective leadership, and intrinsic motivation promotes consistent OCB. The practical implication of this study highlights the importance for the management of PT. BPR BKK Kendal to continuously develop policies that support work-life balance, responsive leadership, and intrinsic motivation to enhance productivity, engagement, and employee loyalty. However, this study is limited to employees of a single rural bank and uses a cross-sectional design, which restricts the generalizability of the findings. Future research is recommended to include additional variables derived from Social Exchange Theory and examine their mediating roles in influencing OCB.